2016
DOI: 10.1002/chem.201602708
|View full text |Cite
|
Sign up to set email alerts
|

Enantiodivergent Synthesis of (+)‐ and (−)‐Pyrrolidine 197B: Synthesis of trans‐2,5‐Disubstituted Pyrrolidines by Intramolecular Hydroamination

Abstract: A highly efficient, diastereoselective, iron(III)-catalyzed intramolecular hydroamination/cyclization reaction involving α-substituted amino alkenes is described. Thus, enantiopure trans-2,5-disubstituted pyrrolidines and trans-5-substituted proline derivatives were synthesized by means of a combination of enantiopure starting materials, easily available from l-α-amino acids, with sustainable metal catalysts such as iron(III) salts. The scope of this methodology is highlighted in an enantiodivergent approach t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 79 publications
0
6
0
Order By: Relevance
“…Furthermore, iron­(III) salts enable the hydrofunctionalization of styrene derivatives or strained alkenes to form carbon–nitrogen, , carbon–oxygen, and carbon–sulfur bonds under different sets of conditions. Similar approaches rely on Brønsted acids, such as trifluoromethanesulfonic acid or those generated in situ from metal triflate salts. In spite of these advances, functionalizing unactivated alkenes with iron­(III) catalysts is limited to intramolecular reactions. Previously, we have disclosed a powerful, yet mild, iron system capable of catalytically activating aliphatic alcohols toward substitution reactions. In our studies of alcohol substitution with sulfonamide nucleophiles, reaction monitoring revealed that cyclohexanol can undergo an iron-promoted E1 elimination, forming cyclohexene . The in situ-generated alkene also proved competent in the reaction.…”
mentioning
confidence: 99%
“…Furthermore, iron­(III) salts enable the hydrofunctionalization of styrene derivatives or strained alkenes to form carbon–nitrogen, , carbon–oxygen, and carbon–sulfur bonds under different sets of conditions. Similar approaches rely on Brønsted acids, such as trifluoromethanesulfonic acid or those generated in situ from metal triflate salts. In spite of these advances, functionalizing unactivated alkenes with iron­(III) catalysts is limited to intramolecular reactions. Previously, we have disclosed a powerful, yet mild, iron system capable of catalytically activating aliphatic alcohols toward substitution reactions. In our studies of alcohol substitution with sulfonamide nucleophiles, reaction monitoring revealed that cyclohexanol can undergo an iron-promoted E1 elimination, forming cyclohexene . The in situ-generated alkene also proved competent in the reaction.…”
mentioning
confidence: 99%
“…Once FeBr 3 was set as the best catalyst, we focused on optimizing the reaction conditions to avoid the formation of pyrrolidine 8 resulting from the intramolecular hydroamination side reaction, whose relative stereochemistry was determined by 1 H-GOESY NMR experiments ( Table 1 ). 36 …”
Section: Resultsmentioning
confidence: 99%
“…1 H NMR spectra were recorded at 400, 500, and 600 MHz, and 13 C NMR spectra were recorded at 100, 125, and 150 MHz, VTU 298.0 K. The residual solvent peak was used as an internal reference (CDCl 3 : δ H 7.26, δ C 77.0). 36 High-resolution mass spectra were recorded on an LCT Premier XE mass spectrometer. It is provided with different ionization sources: electrospray (ESI), an atmospheric pressure chemical ionization (APCI) source, and an orthogonal acceleration time of flight (oa-TOF) analyzer that provides high sensitivity, resolution, and accurate mass measurement.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…A similar transformation was later applied by Wang in cascade reactions implying arylamines and propargylic alcohols catalyzed by FeCl 3 •6H 2 O [59]. In 2016, it was described a highly effective diastereoselective FeCl 3 -catalyzed hydroamidation of α-substituted aminoalkenes derived from enantiopure starting materials, such as amino acids, and this methodology was applied to the enantiodivergent synthesis of (+)and (−)-pyrrolidine 197B [60].…”
Section: Hydroaminationmentioning
confidence: 97%